Enhancing Employee Work Engagement in Health Service through Education and Training - Saferius Ndruru; Eliyunus Waruwu; Maria Magdalena Batee; Forman Halawa (Yayasan Riset dan Pengembangan Intelektual, 2024)
Education and training of human resources are crucial in creating individuals whose potential and skills are in line with the demands of technological developments and are of maximum benefit to the company. This research intends to investigate the influence of education and training simultaneously and partially on work engagement at the Gunungsitoli Health Service. There were 64 employees at the Gunungsitoli Health Service used for the population and sample. A quantitative research method was applied in examining how education and training influence the variables of work engagement. The analysis technique used multiple linear regression. Based on the results, education has, partially, a significant effect on employee work engagement at the Gunungsitoli Health Service. Moreover, education and training simultaneously provide a significant effect on employee work engagement at the Gunungsitoli Health Service. In order to be engaged with their work, the employees require a strong commitment from the Gunungsitoli Health Service to develop their employees through education and training, to strengthen their attachment to their work, and improve overall organizational performance. If education and training are carried out in a programmed manner by the Gunungsitoli Health Service, employee work engagement can be realized. In the initial data collection process, respondents were not honest in providing information, opinions, or answers in the questionnaires distributed. For this reason, it is recommended future researchers should be meticulous when collecting data and information.